Remarkably improved hydrogen storage properties of carbon layers covered nanocrystalline Mg with certain air stability. (23rd October 2020) - Zhang, Liuting; Yan, Nianhua; Yao, Zhendong; Sun, Ze; Lu, Xiong; Nyahuma, Farai Michael; Zhu, Ruihan; Tu, Guoping; Chen, Lixin
Abstract: Different nanocrystalline magnesium with carbon layers were successfully synthesized via a facile wet-chemical ball milling method for 20, 30 and 40 h, respectively. Based on Scherrer formula and X-ray diffraction results, the average crystallite size of all the three samples was below 30 nm. TEM observations showed that the hydrogenated Mg particles were covered with carbon layers. Moreover, the 40 h ball milled Mg sample showed outstanding hydrogen storage performance especially in the aspect of hydrogen absorption. The as-prepared sample started to take up hydrogen at nearly room temperature and eventually absorbed 6.8 wt% hydrogen at 200 °C. The apparent activation energy (Ea ) of hydrogen absorption for the sample was decreased to 26.7 kJ/mol, much lower than that of other reported systems. For the dehydrogenation experiments, the hydrogenated sample could start to release hydrogen at about 275 °C and 6.5 wt% hydrogen was desorbed in 20 min at 325 °C. Interestingly, the prepared samples showed noteworthy air stability. Been placed in the air for 60 min, the dehydrogenation kinetics and hydrogen capacity of the three samples were basically unchanged, making it possible to be used in future commercial applications. Graphical abstract: Nanocrystalline Mg covered with carbon layers synthesized via a facile method showed striking hydrogen storage performance and certain air stability. Image 1 Highlights: Nanocrystalline Mg with carbon layers was prepared via a facile wet chemical milling method. The hydrogenation Ea for the nanocrystalline Mg was dramatically reduced to 26.7 kJ/mol. Hydrogen could be absorbed at 40 °C and released at 275 °C for the nanocrystalline Mg. The as-prepared Mg sample shows superior cycling properties and certain air stability.